2017
DOI: 10.1111/aab.12353
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the virus indexing of Musa germplasm: insights from a multiyear collaboration

Abstract: The Bioversity International Transit Center (ITC) for banana hosts more than 1500 accessions largely covering the genetic diversity of the genus Musa. Its objective is to conserve this genetic diversity and to supply plant materials to users worldwide. All the Musa accessions must be tested for virus presence and, if infected, virus elimination must be attempted, to enable the supply of virus-free plant material. An international collaborative effort launched under the auspices of Bioversity International (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The virus testing is particularly important as several banana growing countries are currently free of damaging viral diseases. The banana bunchy top virus is not present in South America while the banana bract mosaic virus is only present in some Asian countries, and the virus prevalence in collected germplasms reaches 68% (De Clerck et al 2017). Therefore, guaranteeing the movement of pathogen-tested germplasm is an Van den houwe et al CABI Agric Biosci (2020) 1:15 important task to minimize the risk of pest introduction to new countries.…”
Section: Virus Indexingmentioning
confidence: 99%
“…The virus testing is particularly important as several banana growing countries are currently free of damaging viral diseases. The banana bunchy top virus is not present in South America while the banana bract mosaic virus is only present in some Asian countries, and the virus prevalence in collected germplasms reaches 68% (De Clerck et al 2017). Therefore, guaranteeing the movement of pathogen-tested germplasm is an Van den houwe et al CABI Agric Biosci (2020) 1:15 important task to minimize the risk of pest introduction to new countries.…”
Section: Virus Indexingmentioning
confidence: 99%
“…Subsequent investigations have shown that MLBVV is the more probable cause of big-vein disease (Lot et al 2002), but that LBVaV may still be associated with other symptoms such as localised necrosis (Verbeek et al 2013). This eight-decade arc of investigation moved on with advances in diagnostic methods, but ultimately progress was hampered by the limitations of these techniques: Electron microscopy can only observe the morphology of viral particles present, but cannot be used to give a conclusive diagnosis at species level; Biological indexing can give an indication of the pathogens present in a sample, but is prone to failure where a virus is labile or is not amenable to mechanical transmission; Targeted methods can only detect the targets the assays have been designed against, at best a broad number of species in a given genus (Adams et al 2013;De Clerck et al 2017;Rott et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Banana accession ITC0763 from the International Musa Germplasm Transit Centre (ITC) (Bioversity International) presented discrepancies between diagnostic techniques used for indexing when assessed under post entry quarantine in Australia [ 23 ]. No viral symptoms were observed for the accession.…”
Section: Methodsmentioning
confidence: 99%
“…Routine germplasm screening molecular diagnostic tests were carried out on the crude extracts following the procedure described by [ 23 ]. Then, an IC-RT assay was conducted to produce the complementary DNAs, on which the PCR test was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation